BS EN IEC 60502-4. Power cables with extruded insulation and their accessories for rated voltages from 1 kV (Um = 1, 2 kV) up to 30 kV (Um = 36 kV). Part 4. Test requirements on accessories for cables with rated voltages from 6 kV (Um = 7, 2 kV) up to 30 kV (Um = 36 kV) (26th April 2021) - British Standards Institution,
No abstract available